2009
DOI: 10.1021/ol901592f
|View full text |Cite
|
Sign up to set email alerts
|

Swerilactones A and B, Anti-HBV New Lactones from a Tradtional Chinese Herb: Swertia mileensis as a Treatment for Viral Hepatitis

Abstract: Swerilactones A (1) and B (2), two novel lactones with an unprecedented 6/6/6/6/6 pentacyclic ring system, were isolated from the traditional Chinese herb of Swertia mileensis with activity against the hepatitis virus. Their structures and relative stereochemistry were elucidated based on spectroscopic methods and further confirmed by X-ray single crystal diffraction analysis. In vitro antihepatitis B virus (HBV) assay on Hep G 2.2.15 cell line showed that compound 1 inhibited HBsAg and HBeAg secretion with IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…The antiviral agent 3TC (lamivudine) used as positive control showed inhibitory activity against both HBsAg (IC 50 ϭ17.6 mM, S.Iϭ1.5) and HBeAg secretions (IC 50 : 36.2 mM, SIϽ1). 45) An open label clinical observation study reported that an aqueous extract of the flowering tops of Spanish plant Lamium album along with other two herbs were also used in the treatment of HCV (hepatitis C Virus) infections. 100) For evaluation of active anti-HCV principle from this plant, Zhang et al carried out an anti-HCVpp (HCV pseudoparticles) entry essay on both aqueous and MeOH extracts of the flowering tops of the plant and found activity.…”
Section: )mentioning
confidence: 99%
“…The antiviral agent 3TC (lamivudine) used as positive control showed inhibitory activity against both HBsAg (IC 50 ϭ17.6 mM, S.Iϭ1.5) and HBeAg secretions (IC 50 : 36.2 mM, SIϽ1). 45) An open label clinical observation study reported that an aqueous extract of the flowering tops of Spanish plant Lamium album along with other two herbs were also used in the treatment of HCV (hepatitis C Virus) infections. 100) For evaluation of active anti-HCV principle from this plant, Zhang et al carried out an anti-HCVpp (HCV pseudoparticles) entry essay on both aqueous and MeOH extracts of the flowering tops of the plant and found activity.…”
Section: )mentioning
confidence: 99%
“…Interestingly, this investigation resulted in eleven new secoiridoid aglycones including unusual C 9 -skeleton (1-6), bis-C 9 -skeleton (7) and C 10 -skeleton (8)(9)(10)(11) from the low-polarity part of S. mileensis. Structurally, compound 1 belonged to 10-nor-secoiridoid, and compounds 2-6 were attributed to 1-nor-secoiridoids, which further enriched the skeleton types of secoiridoids.…”
Section: Nmr Data For Compounds 6-9 (δ In Ppm J In Hz)mentioning
confidence: 99%
“…[8][9][10] As an ongoing search for anti-hepatitis B virus (anti-HBV) active compounds from natural resources, our recent investigation on the active part of S. mileensis resulted in a series of novel lactones, swerilactones A-O and swerilactosides A-C. [11][12][13][14][15][16][17] From a biosynthetic perspective, swerilactones A and B (C 18 skeleton) were derived from two C 9 secoiridoids, and swerilactones H-K (C 29 skeleton) were condensed by two C 10 and one C 9 secoiridoids. In addition, swerilactone G and swerilactosides A and B also contained the characteristic C 9 secoiridoid moieties in their structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Its congener plant S. mileensis, well-known as Qing-Ye-Dan in Chinese, has been documented in Chinese Pharmacopoeia (1977-2005 editions) for treatment of viral hepatitis. 3 Our previous investigation on S. mileensis resulted in a series of novel anti-HBV active secoiridoid dimers with C 18 and C 20 skeletons (swerilactones A and B 4 , C and D 5 ) and secoiridoid trimers with C 29 skeleton (swerilactones H-K) 6 , as well as three unusual aromatic lactones (swerilactones E-G) 7 and three new secoiridoid glycoside dimers (swerilactosides A-C) 8 . Presently, xanthones, triterpenoids and sterols except for iridoids have been reported from S. kouitchensis.…”
Section: Introductionmentioning
confidence: 99%